Correlações entre biofilme e condição gengival em diferentes frequências de higiene bucal - David, Silvia Cardoso de (2016)
Gingivitis is the most prevalent form among periodontal diseases. Evidence has shown the importance of gingivitis as a precursor of periodontal attachment loss and tooth loss. Despite its importance, often the diagnosis of gingival inflammation is overlooked. For maintaining gingival health, biofilm mechanical removal procedures should be perfomed effectively and periodically. Studies have shown oral hygiene frequencies of 12 and 24h are related to the gingival health maintenance. As important as frequency, it is the quality in which the procedure is performed. Studies assessing the association between toothbrushing frequency, effective biofilm removal and gingival clinical changes have an important role in the prevention and treatment of gingivitis. The aim of this study was to evaluate correlation between plaque and gingival inflammation in individuals underwent effective biofilm control at different frequencies. Data from this study were collected from a randomized clinical trial conducted in 2012 in Santa Maria, RS, Brazil. The sample consisted of 52 UFSM students, of courses not related to health, initially randomized into 4 oral hygiene frequencies and grouped into 2: Group G12/24 (12 and 24h) and group G48/72 (48 and 72h). In G12/24, even with an increase in plaque levels during 30 days, gingival inflammation levels were not statistically different from baseline. In G48/72, increase in plaque levels were accompanied by increasing levels of gingival inflammation. Positive correlation was observed in both groups, however, correlation is reduced in G12/24, demonstrating that increase in plaque levels were not sufficient to develop inflammatory response. In subjects who perform effective biofilm control, the correlation between plaque and gingival inflammation is affected by oral hygiene frequency.